The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18502/kss.v3i11.3999
|View full text |Cite
|
Sign up to set email alerts
|

Youth Perception Toward Their Traditional Culinary: A Study of Minangkabau Culinary Brand Image

Abstract: Based on our previous research, we found that young people in West Sumatra have a tendency to choose modern snacks over the traditional food based on its Brands and Packaging, even though they feel that traditional food was more appropriate to their taste. This study aims to analyze the influence of (1) Brand Perception, (2) Packaging Perception, and (3) Perceived Quality toward the Brand Image of Minangkabau culinary. The population of this study was the Minangkabau Youth in Padang, Padang Panjang, Payakumbuh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…While the research respondents were tourists visiting tourist destinations in the sample cities / regencies. The number of respondents was determined by 500 people proportionally in each sample Regency / City(Susi Evanita & Okki Trinanda, 2017;Trinanda & Evanita, 2019). Meanwhile, the sampling technique (respondents) at each tourist destination was carried out using the Accidental method of distributing the research questionnaire to the visiting tourists who happened to be found during the research(S. Evanita & O. Trinanda, 2017a, 2017b.…”
Section: Methodsmentioning
confidence: 99%
“…While the research respondents were tourists visiting tourist destinations in the sample cities / regencies. The number of respondents was determined by 500 people proportionally in each sample Regency / City(Susi Evanita & Okki Trinanda, 2017;Trinanda & Evanita, 2019). Meanwhile, the sampling technique (respondents) at each tourist destination was carried out using the Accidental method of distributing the research questionnaire to the visiting tourists who happened to be found during the research(S. Evanita & O. Trinanda, 2017a, 2017b.…”
Section: Methodsmentioning
confidence: 99%
“…For the them, culinary is a form of cultural expression . Eating is seen as an important part of the culture [1]. The proximity of culture and cuisine can be seen from various customs, ranging from traditional gatherings, marriage proposals, to casual events, almost all of which involve food.…”
Section: Introductionmentioning
confidence: 99%